2000
DOI: 10.1001/archderm.136.12.1536
|View full text |Cite
|
Sign up to set email alerts
|

Combination Regimens of Topical Calcipotriene in Chronic Plaque Psoriasis

Abstract: To examine the efficacy and tolerability of calcipotriene combined with phototherapy or systemic therapies compared with monotherapy for the treatment of chronic plaque psoriasis.Design: Quantitative systematic review of 11 randomized controlled trials involving a total of 756 patients with plaque psoriasis.Main Outcome Measures: Rate ratios (RRs) for marked improvement or clearance in patient and investigator overall assessments of response; mean difference in percentage change in Psoriasis Area and Severity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
2

Year Published

2002
2002
2018
2018

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 22 publications
0
16
0
2
Order By: Relevance
“…Concomitant acitretin and calcipotriene increase therapeutic efficacy and reduce acetretin dosage. In a meta-analysis of studies of calcipotriene combination therapy, Ashcroft et al 48 found that this acitretin-calcipotriene regimen was more likely to achieve marked improvement than was acitretin alone. Van de Kerkhof et al 78 found that clearance was achieved with significantly lower cumulative dosages of acitretin in patients receiving acitretin and calcipotriene than in those receiving acitretin and placebo (P ϭ .006).…”
Section: Systemic Agents In Combination With Topical Agentsmentioning
confidence: 99%
“…Concomitant acitretin and calcipotriene increase therapeutic efficacy and reduce acetretin dosage. In a meta-analysis of studies of calcipotriene combination therapy, Ashcroft et al 48 found that this acitretin-calcipotriene regimen was more likely to achieve marked improvement than was acitretin alone. Van de Kerkhof et al 78 found that clearance was achieved with significantly lower cumulative dosages of acitretin in patients receiving acitretin and calcipotriene than in those receiving acitretin and placebo (P ϭ .006).…”
Section: Systemic Agents In Combination With Topical Agentsmentioning
confidence: 99%
“…7,14 Combination regimens that include oral retinoids are attractive because the addition of a second or even third agent augments efficacy. 15,16 While minor adverse effects may be common at high doses, these may be managed by dose reduction as part of a combination regimen. Unfortunately, we do not have data on doses used when a medication was used as monotherapy versus in a combination regimen.…”
Section: Discussionmentioning
confidence: 99%
“…Calcipotriol has been previously shown to be well tolerated and efficacious in combination with numerous other psoriatic treatments, including topical therapies [13], phototherapy [15, 16]and systemic therapy [13, 14]. A study was carried out to investigate the addition of calcipotriol ointment (50 µg/g) to systemic retinoid acitretin therapy in psoriasis [14].…”
Section: Discussionmentioning
confidence: 99%
“…Calcipotriol has been demonstrated to be equivalent to or more effective than dithranol [8], coal tar [9]and at least as effective as steroids [10, 11]. It is effective in the long term [12]and has been successfully used in combination with systemic treatments [13, 14]and, as well as other vitamin D 3 derivatives, with phototherapy [15, 16, 17]. Calcipotriol is well tolerated, even in children [18], with no effect on hepatic or renal function or calcium haemostasis [19].…”
Section: Introductionmentioning
confidence: 99%